P255Galectin-3: a new promising cardiac biomarker in sports endurance?. (15th July 2014) - Le Goff, C; Devaux, S; Brevers, E; Peeters, S; Kaux, JF; Cavalier, E
Abstract: Purpose: Galectin-3 (Gal-3) is well-known as a very interesting biomarker for heart failure and myocardial fibrosis. Gal-3 is a carbohydrate binding lectin produced by macrophages, upregulated in hypertrophied heart, emerging as an important mediator for fibrosis development and cardiac remodeling. We aimed to examine the evolution of Gal-3 in some endurances runners compared to sedentary subjects and the correlation of its evolution with other cardiac and renal biomarkers. Methods: Twenty-eight males (mean age 37 ± 8.5 yo), 9 healthy non-elite marathon runners (42 km), 10 ultratour runners (67 km) and 9 sedentary subjects (10 km, <2h of sport/week). Blood samples were taken just before (T0), just after (T1) and 3 hours (T3) after the race. The biomarkers used for the correlation were: highly sensitive troponin T (TnThs), N-terminal-pro brain natriuretic peptide (NT-proBNP), myoglobin (MYO), myeloperoxydase (MPO), cystatine C (CYSC), creatinin (Cr). The analyses were performed on the VIDAS (Biomerieux) and COBAS (Roche Diagnostics) according to the manufacturer's specifications. The study was approved by the Ethical Committee of our University Hospital. Results: The concentration of all biomarkers measured in the post-race (T1 and T3) samples was remarkably increased, compared with the values obtained on baseline (T0) specimens. Plasma Gal-3 increased from baseline to post exercise and decreased in the 3 hours after the end of the exercise. Indeed, at T1, we observed that the level is higher in marathon runner (mean at T1 = 25 ± 5.08 ng/ml) than in ultratour (mean at T1 = 18.7 ± 4.45ng/ml) and in the sedentary runners (mean at T1 = 11.88 ± 2.09 ng/ml). The concentrations obtained for the marathon runners at T1 could be considered as a risk predictor of cardiovascular event in the general population. Interestingly, baseline plasma levels of Gal-3 were in normal range but higher than in healthy sedentary controls. There is a correlation between the increase of Gal-3 and TnThs, NT-proBNP, MYO, MPO, CYSC, Cr. Conclusions: The results of this study demonstrate that exercises of different intensity are associated with biochemical abnormalities that may reflect adverse consequences on cardiac structure as fibrosis and biology.